Student Perception towards Personal Branding of Political Leaders on Twitter Ahead of Presidential Election 2014 - Bita Asrining Wulan; Suryadi Suryadi; Bambang Dwi Prasetyo (Wacana Journal of Social and Humanity Studies, 2014)
Recent technology developments bring improvement for communication studies. Computer mediated communication (CMC) theory ispotential to rapid messages send using computer with internet connection. Twitter is one of well-known social media, which is used by large number of societies, including our president candidates, e.g. Prabowo Subianto and Aburizal Bakrie. Majority twitter users are teenagers, because teenagers are active society and they use twitter to let themselves know about their upcoming president. Active society had explained in uses and gratification theory. This study aims to identify college student’s perception about politician’s personal branding on twitter lately before the election on 2014. This research is a descriptive research which used qualitative approach, and equipped with content analysis. This research usednon probability sampling to select the main informants, and also snowball sampling method. Results show that college student’s perceptionstowards Prabowo Subianto’s twitter were better than their perceptions to Aburizal Bakrie’s although Aburizal twitter’s management is much betterand friendly. Active and positive responses from college students didn’t influenced by politician’s personal branding. There are eight concepts in personal branding, known as the eight of law of personal branding. From the eight concepts, Prabowo Subianto known as a well behavior person with high nationalism while Aburizal Bakrie had very well law of visibility in twitter’s management.Key words : Perception of college students as twitter user, Politician’s Personal Branding